Scaling climate information services to reach over 100,000 farmers in Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate variability can have tremendous negative effects on farmers. Therefore, CCAFS and partners established Local Technical Agroclimatic Committees (LTACs) in Latin America to help them properly predict the weather so that crop losses can be minimized.